The Severity of Acetabular Retroversion Does Not Influence Outcomes of Arthroscopic Management of FAI. Issue 7 (30th July 2021) - Day, Molly; Seiffert, Kayla; An, Qiang; Larson, Christopher; Westermann, Robert
Objectives: Controversy exists regarding optimal treatment of FAI in the setting of acetabular retroversion. The purpose of this study was to investigate changes in pain and function among patients with acetabular retroversion treated with hip arthroscopy. Secondarily, to assess if the severity of posterior wall deficiency influences post-operative outcomes following hip arthroscopy. Methods: A retrospective review of patients with acetabular retroversion with hip arthroscopic surgery at a single institution was performed. Acetabular retroversion was defined by three radiographic criteria: the presence of crossover sign, ischial spine sign, and posterior wall sign. Anteroposterior radiographs were used to measure lateral center edge angle (LCEA), Tonnis grade, anterior wall index (AWI) and posterior wall index (PWI), and alpha angle. Patient-reported outcome (PROs) included modified Harris Hip Score (MHHS), visual analog scale (VAS) and quality of life with Veterans RAND-12 (VR-12). Spearman correlation coefficients were used to determine correlation of PWI with pre- and post-PROs. Multivariate analysis was performed and generalized estimating equation was used to determine independent predictors for outcome scores. Significance was set at p<0.05. Results: Between 2013 and 2019, 138 patients with FAI and acetabular retroversion underwent hip arthroscopy, 67% were female. The average follow-up was 29 months, with minimum of 6 months. Average preoperative LCEA 28, alpha angle 70.1, postoperative alpha angle 44.6 (p<0.05). All PROs demonstrated significant improvement from preoperative baseline to follow-up scores (MHHS (59.5 +/- 14.7 vs 80.8 +/- 18.8), VAS (6.3 +/- 1.7 vs 3.0 +/- 2.7), p<0.0001). Four patients (3%) underwent revision procedures. Upon multivariate analysis, no association between PWI and PROs was not found. Preoperative mHHS was the strongest predictor of clinical outcome. Conclusions: This is the largest study of patients with acetabular retroversion assessing for a correlation between PWI on patient-reported outcomes following arthroscopic management of FAI. In patients with acetabular retroversion, outcomes are good following arthroscopic management with low complication and revision rate following hip arthroscopy. Posterior wall deficiency was not a predictor of poor outcome in patients with acetabular retroversion. In this single surgeon selected series, the severity of retroversion (measured by PWI) does not appear to have a threshold or any correlation with postoperative outcomes in following FAI treatment.